Achieving energy security in Asia diversification, Integration & Policy Implications - Taghizadeh-Hesary, Farhad; Yoshino, Naoyuki 1950 -; Chang, Youngho (2019)
This book presents a critical review of the status of energy security in Asia and suggests how a country or a region collectively can achieve energy security in two broad aspects. First, it analyzes how regional cooperation and energy trade can enhance energy security in the region. Second, it reviews how energy security can be ensured in national and regional general contexts. From the reviews and analyses, this book asserts that diversification and integration are key to ensuring energy security. It presents policy implications for enhancing energy security, especially in resource-rich as well as resource-poor developing countries in Asia.